FAP-targeted SPECT/CT and PET/CT imaging for breast cancer patients - McGale, Jeremy; Khurana, Sakshi; Howell, Harrison; Nakhla, Abanoub; Roa, Tina; Doshi, Parth; Shirini, Dorsa; Huang, Alice; Duong, Phuong; Backhaus, Philipp; Liao, Matthew; Kaur, Harleen; et al. (Clinical nuclear medicine, 2025)
Breast cancer presents a significant global health challenge, necessitating continued innovation in diagnostic and therapeutic approaches. Recent advances have led to the identification of cancer-associated fibroblasts, which are highly prevalent in breast cancers and express fibroblast activation proteins (FAPs), as critical targets. FAP-specific radiotracers, when used with PET/CT and SPECT/CT, have significant potential for improving early breast cancer detection, staging, treatment response monitoring, and therapeutic intervention. This review provides insight into FAP-targeted molecular imaging, exploring advanced techniques for protein status assessment, development of early-phase targeted therapies, and other emerging applications. The advent of FAP-targeted imaging stands to significantly enhance personalized oncologic care, leading to improved breast cancer management and overall patient outcomes.